Formação de professores pela/para pesquisa: proposta pedagógica para o seminário interdisciplinar das licenciaturas do IFAM - Ferreira, Danielle Cristina Oliveira (2017)
It is an investigation in the educational field, centered in the undergraduate courses in Biological Sciences, Chemistry, Physics and Mathematics of the Federal Institute of Education, Science and Technology of Amazonas - IFAM, Campus Manaus - Center, with the objective of developing actions to insert Systematically professors of the initial training of the IFAM undergraduate courses in research processes, starting from SEMINTER. For that, it was necessary to elaborate a theoretical reference that presented the foundations to treat the research in the initial formation of teachers; Identify how the research is handled in the pedagogical projects of the IFAM teacher training courses; To elaborate a pedagogical proposal that would characterize the SEMINTER as space to carry out research processes in the initial formation of professors of the IFAM; To evaluate whether the proposal elaborated constitutes a training space for teachers for research. In order to carry out such actions, a methodological course was developed, centered on collaborative research, in which four licensees and sixteen professors working in the bachelor's degrees participated. The following techniques were used: documentary analysis, interview and meeting, and as instruments of data collection: questionnaire, audio recording and meeting minutes. This course allowed the construction of data that were interpreted and made possible the preparation of the SEMINTER proposal, which was submitted to the evaluation of twenty referees, twelve teachers (six internal and six external to the institution) and eight participants (Four undergraduate students and four graduates). The results of the opinions, once analyzed, allowed to construct the final proposal of the SEMINTER, and evidenced that the proposal presents conditions to systematically insert teachers of the initial training of the undergraduate courses of the IFAM in research processes and, in addition, contribute to effective and accompaniment these processes.